A Study of the TikTok Business and Communication Model, Including Its Prospects and Constraints on Youth - Xinyi Sun (Studies in Social Science & Humanities, 2023)
With the rapid development of information technology and the emergence of various digital media platforms, TikTok has gradually become known and appreciated by the public. This study aims to investigate and analyze the collective activities of young users on the TikTok platform, focusing on their profiles, TikTok’s Dissemination Model, and business models. The popularity of TikTok among the youth, especially teenagers, has made it an important platform for them to participate in cultural activities and establish their online presence. By examining existing social science research and utilizing data from TikTok, this study seeks to understand how young users engage with the platform and the role it plays in shaping their activities. Additionally, the study will explore the potential of TikTok as well as the challenges it currently faces in facilitating youth practices.